Dabigatran Associated Leukocytoclastic Vasculitis - Evangelos Potolidis (Case Reports in Medicine, 2015)
Common side effects of dabigatran are bleeding, bruising, nausea, diarrhea, and abdomen discomfort. Skin reactions were not often noted (<0.1%). We report a case of 70-year-old male who developed dabigatran related skin reaction resistant to usual therapy. Skin biopsy revealed leukocytoclastic vasculitis.